Self-confidence and level of knowledge after cardiopulmonary resuscitation training in 14 to 18-year-old schoolchildren: A randomised-interventional controlled study in secondary schools in Germany. Issue 7 (July 2018) - Wingen, Sabine; Schroeder, Daniel C.; Ecker, Hannes; Steinhauser, Susanne; Altin, Sibel; Stock, Stephanie; Lechleuthner, Alex; Hohn, Andreas; Böttiger, Bernd W.
Abstract : BACKGROUND: Education of schoolchildren in cardiopulmonary resuscitation (CPR) is a strategic goal for improvement of bystander CPR in society. OBJECTIVE(S): The primary objective was to analyse the impact of CPR training on the resuscitation knowledge and self-confidence of secondary schoolchildren. In addition, independent predictors of improved CPR knowledge and self-confidence were investigated. DESIGN: Randomised-interventional controlled study. SETTING: Four secondary schools in Germany. PARTICIPANTS: Four hundred and twenty-four schoolchildren aged from 14 to 18 years were included into the study. Fifty-one percent were female, and 33% had an immigrant background. INTERVENTION: The intervention group received a 90-min CPR training session, whereas controls had no intervention. Levels of knowledge and self-confidence in initiating CPR were analysed by a study questionnaire before ( t 0 ), 90 min after ( t 1 ) and 6 months after training ( t 2 ). MAIN OUTCOME MEASURES: Based on the evaluation of study questionnaires, the primary endpoint was to determine the development of resuscitation knowledge and self-confidence in initiating cardiopulmonary resuscitation at survey time-points t 0, t 1 and t 2 . RESULTS: Schoolchildren in the intervention group ( n =207) showed a significantly higher level of knowledge ( P  < 0.001) and self-confidence ( P  < 0.001) at t 1 and t 2 compared with controls ( n =217). Age was a predictor for long-term self-confidence [odds ratio (OR), 1.20; 95% confidence interval (95% CI), 1.02 to 1.41; P  = 0.032]. The long-term benefit in the level of knowledge and self-confidence were significantly higher in native compared with immigrant schoolchildren: (OR, 1.79; 95% CI, 1.14 to 2.82; P  = 0.011) and (OR, 1.67; 95% CI, 1.07 to 2.60; P  = 0.024), respectively. CONCLUSION: Guideline compliant (90 min) theoretical and practical CPR training improves the level of knowledge and self-confidence in 14 to 18-year-old schoolchildren. Older schoolchildren are more likely to have increased self-confidence with respect to initiating CPR. Schoolchildren with an immigrant background showed a significantly lower increase in their level of knowledge and self-confidence compared with native children. Adaptation and simplification of teaching materials and further research on educational methods for CPR are urgently needed to enable a sustainable approach to teaching CPR, which also produces a long-lasting effect in the entire population.